ANALYSIS OF THE REAL ESTATE MARKET IN ROMANIA FROM THE POINT OF VIEW OF THE NUMBER OF TRANSACTIONS DURING 2009-2018 - Paul Cosmin Alin ENACHESCU; Genifera Claudia BANICA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2019)
During the years 2009-2018, at the same time with the minimum interest rates, the increase of the gross disposable income and the GDP/inhabitant, the real estate investments became the safest. In the absence of an integrated database that raises the transparency of the real estate market in Romania, the main indicators are statistics on the dynamics of transactions and demographic indicators. This study involves a comprehensive analysis and correlation of statistical data to determine the links that contributed to the dynamics of the Romanian real estate market during 2009-2018. Without going through the extensive list of causes that have contributed to the dynamics of the market, a number of factors such as legislative, technological, demographic, micro and macroeconomic, attest that the level of real estate transactions can represent a good indicator of the economic situation. Once the Romanian economy showed signs of recovering from the last international economic crisis, and the purchasing power increased, the volume of real estate transactions began again. During the analyzed period, despite the fluctuation of the number of transactions, annually, the obtainable price of the properties increased fluctuating. However, the dynamics of transactions in 2018 fell below the values before the economic crisis.